Mixed orbital states and modulated crystal structures in La1-xCaxMnO3 deduced from synchrotron X-ray diffraction - Pissas, M.; Stamopoulos, D.; Prassides, K. (COMMUNICATIONS PHYSICS, 2023)
Doped lanthanum manganite compounds exhibit a range of conducting, electronic and magnetic phases, and, in the case of the Ca-doped series, a phase transition from a ferromagnetic metal to an antiferromagnetic insulator occurs. Here, the authors use ultrahigh-resolution synchrotron X-ray diffraction to track the complex structural behavior of La1-xCaxMnO3 below the charge-ordering temperatures. In the model manganese perovskites La1-xCaxMnO3, several important phenomena have been observed, including ferromagnetic metallic/insulating states, colossal magnetoresistance effects, and charge- and orbital-ordered states. In the past, only compounds with x = 1/2, 2/3 and 3/4 and an insulating ground/antiferromagnetic state have been studied. To fully understand the crystal and electronic structures of these materials, it is important to study compounds with doping levels in the range of 0.5 < x < 2/3. Here we study the crystal structure in a series of compounds with 0.5 < x & LE; 0.6 using ultrahigh-resolution synchrotron X-ray diffraction. The experimental results reveal that all compounds undergo a structural transition at T < T-CO(x) & AP; 200 - 220 K with the concomitant emergence of superlattice Bragg peaks, which can be indexed assuming a superstructure with a modulation propagation vector, & tau;. At the base temperature of 5 K, the modulation vector of the superstructure & tau; = [& tau;(a), 0, 0] is parallel to the a-axis, with & tau;(a) varying linearly with x, as & tau;(a) & AP; 1 - x. Our results may aid attempts to understand more deeply phenomena related to spin, charge, and orbital ordering, as well as colossal magnetoresistance and symmetry breaking and emergent order in quantum states.